Frequency of Class I and II HLA alleles in patients with lung cancer according to chemotherapy response and 5-year survival - (:unkn) unknown (WILEY-BLACKWELL, 2015)
IntroductionLung cancer is the most common cause of cancer death in the world, and the most common type is non-small-cell lung cancer (NSCLC). At present, surgical resection, chemotherapy, and radiation therapy are the main treatments for patients with NSCLC, but unfortunately outcome remains unsatisfactory. ObjectivesThis study aimed to determine whether Class I and II histocompatibility leukocyte antigen (HLA) alleles are related with response to chemotherapy and survival of lung cancer. MethodsA total of 65 NSCLC patients (56 men and 9 women, mean age 58.411years) were included in the study. Patient groups were compared with a control group of 88 unrelated healthy kidney or bone marrow donors in order to clearly identify susceptible and protective HLA alleles in lung cancer. Target lesions and tumor response were assessed using the Response Evaluation Criteria for Solid Tumors (RECIST) guidelines. Results were classified into two groups: complete-partial response and stable-progressive disease. ResultsWe found that expression of HLA-A32, HLA-B41, HLA-B57, HLA-DRB1*13, and HLA-DQ5 were more frequent in the complete and partial response groups to chemotherapy than in the control group. The frequency of HLA-A11, HLA-A29, HLA-BW6, HLA-CW3, HLA-DR1*1, and HLA-DRB1*3 were determined to be higher in the stable and progressive disease groups taking chemotherapy than in the control group. Additionally, expressions of HLA-A2 and HLA-B49 were statistically related with 5-year survival. ConclusionOur results suggested that expressions of HLA-BW6 and HLA-DRB1*13 alleles may be predictable markers for response to chemotherapy in lung cancer patients.
Keywords: Class I and II HLA alleles; lung cancer; response to chemotherapy; survival; INFLAMMATORY FACTOR-I; PROGNOSTIC-FACTOR; DRUG-RESISTANCE; SOLID TUMORS; EXPRESSION; ANTIGEN; CARCINOMA; VIVO; PROLIFERATION; INTERFERON